Association of UBQ-8i polymorphism with Alzheimer's disease in Caucasians: a meta-analysis. (1st June 2015) - Yue, Zhen; Wang, Sen; Yan, Weiping; Zhu, Fengyi
<x xml:space="preserve">Abstract</x> Background: Several studies have reported an association between the UBQ-8i (rs12344615) polymorphism of the UBQLN1 gene and risk of Alzheimer's disease (AD), but these findings remain controversial. In this study, a meta-analysis was carried out to investigate the relationship between UBQ-8i polymorphism and AD risk and a possible synergy with apolipoprotein E (APOE)ε4 gene status. Methods: Case–control studies were selected from PubMed, Medline and Embase (Ovid) databases. The potential association was evaluated by odds ratios (ORs) with 95% confidence intervals (CIs). Data were analyzed with Stata version 11.0. Results: A total of 4679 AD cases and 9928 controls were included in the study. There was no evidence of heterogeneity between studies or publication bias in the meta-analysis. There were no significant differences among the examined genetic models. In the analysis stratified by age of onset, a significant association was detected in the late onset AD group under the allele (OR = 1.12, 95% CI: 1.01–1.24), heterozygote (OR = 1.15, 95% CI: 1.02–1.30) and dominant (OR = 1.13, 95% CI: 1.00–1–26) models. However, UBQ-8i polymorphism was not associated with a higher risk for AD among APOEε4 carriers. Conclusion: The results suggest that UBQ-8i polymorphism may contribute to AD susceptibility, but does not synergize with APOEε4 status to increase AD risk.